Control as part of the management system of internal processes - Popko, O.; Golovash, B. (Ways to Improve Construction Efficiency, 2020)
Enterprise management – is the process of planning, organization, motivation, control and regulation of personnel actions, setting strategic goals and tactical objectives of the enterprise, making management decisions and ensuring their implementation. Control, in the process of managing the activities of the enterprise, is an extremely important element in the system of mechanisms that provide the efficiency of the enterprise. Control is a process that helps an organization achieve its goals. Control continues the planning process and monitors the implementation of plans. One of the essential functions of control is to determine the reserves for new management decisions. The authors in the article define the organizational and legal forms of ensuring the implementation of internal control procedures. The authors present one of the elements of the management system of the relevant processes (control) and describe its factors that affect them. The authors give a clear definition of the concept of control system at the enterprise (internal control) as part of the management system of internal processes and characterize the components of the internal control structure, methods of their analysis and analyze its quality and feasibility in the current realities of enterprises. Enterprise financial management includes the organization and control of cash inflows from sales of products or collection of amounts under previous agreements for services rendered, as well as cash inflows from securities, and etc. The most important tasks of financial management are also the payment of supplies of raw materials and materials intended for production; payments on invoices payable for previously purchased goods; payments for operating costs (advertising, insurance, etc.); payment of wages to employees of the enterprise; payment of taxes and other payments to the budget and extrabudgetary funds. The article determines that the effectiveness of control of such an organizational system as the enterprise management system should be characterized by special indicators. These indicators are influenced by a large number of external and internal factors, and it is desirable to assess them with a limited number of criteria.